216k views
5 votes
(4/3)^1-x = e^x (solve exponential equation)

User Raz Mahato
by
6.4k points

1 Answer

3 votes

we are given


((4)/(3) )^(1-x)=e^x

Since, we have to solve for x

so, firstly we will isolate x on any one side

we can take ln on both sides


ln(((4)/(3) )^(1-x))=ln(e^x)

now, we can simplify it


(4-x)ln(((4)/(3) )=x

now, we can move all x terms altogether


4*ln((4)/(3))-xln((4)/(3))=x


xln((4)/(3))+x=4*ln((4)/(3))


x(ln((4)/(3))+1)=4ln((4)/(3))

so, we get


x=(4ln((4)/(3)))/((ln((4)/(3))+1))...........Answer

User Sumnulu
by
5.9k points